2020
DOI: 10.7554/elife.56523
|View full text |Cite
|
Sign up to set email alerts
|

DAZL mediates a broad translational program regulating expansion and differentiation of spermatogonial progenitors

Abstract: Fertility across metazoa requires the germline-specific DAZ family of RNA-binding proteins. Here we examine whether DAZL directly regulates progenitor spermatogonia using a conditional genetic mouse model and in vivo biochemical approaches combined with chemical synchronization of spermatogenesis. We find that the absence of Dazl impairs both expansion and differentiation of the spermatogonial progenitor population. In undifferentiated spermatogonia, DAZL binds the 3' UTRs of ~2,500 protein-coding genes. Some … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 122 publications
(249 reference statements)
1
27
0
Order By: Relevance
“…Notably, the UGUU(U/A) motif is identified in most predicted DAZL interacting genes. This motif is recently reported as the most preferential motif for DAZL binding than all other motifs mentioned above [ 17 ]. Moreover, the longer 3’UTRs contained more counts, and the shorter 3’UTRs contained fewer counts of the DAZL binding motifs.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Notably, the UGUU(U/A) motif is identified in most predicted DAZL interacting genes. This motif is recently reported as the most preferential motif for DAZL binding than all other motifs mentioned above [ 17 ]. Moreover, the longer 3’UTRs contained more counts, and the shorter 3’UTRs contained fewer counts of the DAZL binding motifs.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, we analyzed the DAZL interacting genes in this study based on the conserved DAZL binding motifs reported in other species. In the results, we identified different counts of the reported DAZL binding motifs, such as UGUU(U/A) [ 17 ], UGUU [ 16 ], GUU(U/A) [ 17 ], GUUG [ 13 ], GUUC [ 26 ], and UUU(C/G)UUU [ 15 , 27 ], in the 3’UTR of the predicted DAZL interacting genes in chicken ( Table S1 and Figure S1 ). Notably, the UGUU(U/A) motif is identified in most predicted DAZL interacting genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations